Upconversion Cross-Correlation Spectroscopy of a Sandwich Immunoassay - Lahtinen S; Krause S; Arppe R; Soukka T; Vosch T (WILEY-V C H VERLAG GMBH, 2022)
Fluorescence correlation and cross-correlation spectroscopy (FCS/FCCS) have enabled biologists to study processes of transport, binding, and enzymatic reactions in living cells. However, applying FCS and FCCS to samples such as whole blood and plasma is complicated as the fluorescence bursts of diffusing labels can be swamped by strong autofluorescence. Here we present cross-correlation spectroscopy based on two upconversion nanoparticles emitting at different wavelengths on the anti-Stokes side of a single excitation laser. This upconversion cross-correlation spectroscopy (UCCS) approach allows us to completely remove all Stokes shifted autofluorescence background in biological material such as plasma. As a proof of concept, we evaluate the applicability of UCCS to a homogeneous sandwich immunoassay for thyroid stimulating hormone measured in buffer solution and in plasma.